2021
DOI: 10.3390/genes12050638
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Processes during Early Development of Dictyostelium discoideum: From Bioenergetic to Proteomic Studies

Abstract: The slime mold Dictyostelium discoideum’s life cycle includes different unicellular and multicellular stages that provide a convenient model for research concerning intracellular and intercellular mechanisms influencing mitochondria’s structure and function. We aim to determine the differences between the mitochondria isolated from the slime mold regarding its early developmental stages induced by starvation, namely the unicellular (U), aggregation (A) and streams (S) stages, at the bioenergetic and proteome l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This method was different from our earlier CK profiling assessing early development, for which cells were starved for 6 h in KK2, and samples were collected with distinct streams and aggregation centers 13 . A recent publication assessing mitochondrial dynamics in vegetative growth and early development in D. discoideum through bioenergetics and proteomics found that the main mitochondrial processes are downregulated during early development and that there was less mitochondrial yield overall in early developmental samples compared to vegetative cells 73 . Therefore, sampling a larger population of cells in early development may have helped make the findings in mitochondrial content more comparable to what was analyzed in the vegetative samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was different from our earlier CK profiling assessing early development, for which cells were starved for 6 h in KK2, and samples were collected with distinct streams and aggregation centers 13 . A recent publication assessing mitochondrial dynamics in vegetative growth and early development in D. discoideum through bioenergetics and proteomics found that the main mitochondrial processes are downregulated during early development and that there was less mitochondrial yield overall in early developmental samples compared to vegetative cells 73 . Therefore, sampling a larger population of cells in early development may have helped make the findings in mitochondrial content more comparable to what was analyzed in the vegetative samples.…”
Section: Discussionmentioning
confidence: 99%
“…13 A recent publication assessing mitochondrial dynamics in vegetative growth and early development in D. discoideum through bioenergetics and proteomics found that the main mitochondrial processes are downregulated during early development and that there was less mitochondrial yield overall in early developmental samples compared to vegetative cells. 73 Therefore, sampling a larger population of cells in early development may have helped make the findings in mitochondrial content more comparable to what was analyzed in the vegetative samples. Sampling after the streaming and aggregation centers have formed would provide an insightful follow-up to this analysis.…”
Section: Ipta-deficiency and Overexpression Downregulates Amino Acid ...mentioning
confidence: 99%
“…Despite the growing interest in using D. discoideum as a model organism to study many conserved mitochondrial processes and some unique biology, a comprehensive list of the mitochondrial proteins has yet to be established. A recent proteomic study detected 294 proteins in D. discoideum mitochondria ( Mazur et al., 2021 ), which we believe is far from complete. Nuclear-encoded mitochondrial proteins, which constitute over 90% of the total mitochondrial proteome, are synthesized in the cytoplasm and then imported to mitochondria.…”
Section: Introductionmentioning
confidence: 85%